Using cost-effectiveness analysis to support policy change: varenicline and nicotine replacement therapy for smoking cessation in Jordan - Saba Madae’en (Journal of Pharmaceutical Policy and Practice, 2020)
Abstract Background Smoking cessation pharmacotherapies (SCPs) have been established as cost-effective for the treatment of tobacco use disorder across a variety of settings. In Jordan, a resource-constrained country where smoking rates rank at one of the highest globally, the cost-effectiveness of SCPs has not yet been quantified. The lack of information about the value of SCPs has contributed to low demand for them (from public and private payers) and consequently low availability of these medications. The aim of this study was to simulate—in a hypothetical cohort of Jordanian smokers—the clinical and economic impact of using two smoking cessation regimens and to generate cost-effectiveness values that can support policy changes to avail smoking cessation medication in a country burdened with heavy tobacco use. Methods We employed a similar approach to a widely used economic model, the Benefits of Smoking Cessation on Outcomes (BENESCO) model. A hypothetical cohort of Jordanian male smokers aged 30 to 70 years and making a quit attempt using either a varenicline regimen or a nicotine replacement therapy (NRT) regimen were followed over time (until reaching 70 years of age). Markov simulations were run for the cohort, and life years gained were computed for each arm (compared to no intervention). Drug costs, prevalence of smoking, and population life expectancies were based on Jordanian data. Efficacy data were obtained from the literature. Incremental cost-effectiveness ratios as well as the potential budgetary impact of employing these regimens were generated. Several parameters were modified in sensitivity analyses to capture potential challenges unique to Jordan and that could impact the results. Results For a treatment cohort of 527,118 Jordanian male smokers who intended to quit, 103,970 life years were gained using the varenicline regimen, while 64,030 life years were gained using the NRT regimen (compared to the no-intervention arm of life years). The cost per life year gained was JD1204 ($1696 USD) and JD1342 ($1890 USD) for varenicline and NRT, respectively.